(untitled) (ENTHYMEMA, 2023)
The article reports, partially reworks, often annotates, the answers by eleven ‘electronic writers’ to questions related to Literature&Internet. The article does not intend to define a phenomenon, such as that of ‘electronic literature’, that is broad, heterogeneous, complex and mutant by definition, but it rather tries to testify along (but also among and beyond) the way, the divergent/converging paths and the opinions of those who has been trying to ‘make’ electronic literature ‘inside the net’ for the past thirty-five years. Between the faults/faille of these not-sewn-properly fragments, flashes of a context leak out, in which literature fai(l/nt)s, going beyond the representation (of the spectacle of meaning) to become the (occult) scenario of unexpected events. In the absurdist laboratory of this literature finally willing to play of/in itself, the threads of the net are made and unmade; a net that does not catch nor contains; a net of (making) doing and not (only) of saying.